Mellanskogs medlemmars syn på röjning - Jansén, David (SLU/School for Forest Management, 2011)
The main purpose of this study is to investigate the needs of pre-commercial thinning on private owned forest properties, which is considered to be increasing. The reason is believed to be the high cost of labor that pre-commercial thinning brings. Furthermore thinning is costly, the revenue created through pre-commercial thinning are post-poned until the first thinning. The study was made through a survey among members of Mellanskog forest owners association. The survey was distributed by e-mail. The time to answer was set to two weeks. The answers indicate that the most common reason why the pre-commercial thinning is delayed, or not done at all, is the forest owner’s lack of time. The high cost is also a common reason. The answers to some questions indicate that there is a certain need of advisory service among the owners of small properties, as well as owners that does not live on their property.